Thrombospondin-1: A Key Protein That Induces Fibrosis in Diabetic Complications. (12th June 2020) - Xu, Linhao; Zhang, Yong; Chen, Jian; Xu, Yizhou
Abstract : Fibrosis accompanies most common pathophysiological features of diabetes complications in different organs. It is characterized by an excessive accumulation of extracellular matrix (ECM) components, the response to which contributes to inevitable organ injury. The extracellular protein thrombospondin-1 (TSP-1), a kind of extracellular glycoprotein, is upregulated by the increased activity of some transcription factors and results in fibrosis by activating multiple pathways in diabetes. The results of studies from our team and other colleagues indicate that TSP-1 is associated with the pathological process leading to diabetic complications and is considered to be the most important factor in fibrosis. This review summarizes the molecular mechanism of increased TSP-1 induced by hyperglycemia and the role of TSP-1 in fibrosis during the development of diabetes complications.